Isolation and Identification of Genus Salmonella and Shigella from Sumatran Orangutan (Pongo abelii) Feces in Orangutan Reintroduction Center, Jantho - Erdiansyah Rahmi; Dina Agustina; Faisal Jamin (Jurnal Medika Veterinaria, 2014)
This study was done to identified bacteria of genus Salmonella and Shigella from sumatran orangutan (Pongo abelii) feces. Nine semi wild orangutan fecal samples were obtained in Orangutan Reintroduction Center, Cagar Alam Pinus Jantho, Aceh Besar. The samples were processed using Carter methode. The selective media used were Salmonella Shigella Agar (SSA), Eosin Methylen Blue (EMB), and MacConkey Agar. The separated colonies which grawn in SSA media were observed for their morphology, and followed by Gram staining methode then continued with biochemical test such as Indol, Methyl Red (MR), Voges Proskauer (VP), Sulfid Indol Motility (SIM), Simmons Citrate (SC), and sugar test such as glucose, sucrose, lactose, and manitol. From nine samples, one orangutan was infected with Salmonella and another one was infected with Shigella. All of the samples were identified with Escherichia. In Conclusion, orangutan lived at Reintroduction Center, Jantho infected with Salmonella and Shigella bacteria.Key words: feces, orangutan, Salmonella, Shigella